(untitled) (Ciencias de la Ingeniería y Aplicadas, 2021)
The research carried out in the experimental greenhouse of the Technical University of Cotopaxi on the Salache Campus, had the objective of incorporating the control of humidity, energy and water consumption, through a measurement system with an ultrasonic sensor, PLC S7 1200, a solenoid valve, FC 28 type humidity sensors and an energy meter, which help monitor the behavior of humidity to define irrigation times and perform manual and automatic control of this resource. Where, through the solenoid valve, the filling of the tank is controlled, which is previously programmed with a minimum and maximum level depending on the capacity of the tank. For the personnel in charge of the greenhouse, a graphical interface (HMI) was created, where energy consumption, water consumption and the behavior of the humidity variable can be controlled and monitored remotely, which allows knowing the daily water consumption. , weekly and monthly. In addition, the indicators of the total capacity of the tank in liters, the water level in the tank and the indicator of the liters existing inside the tank are considered. The humidity and water consumption control system contributed to guaranteeing the appropriate water humidity regime in the greenhouse crops and facilitated the monitoring of water consumption by plants to achieve a correct dosage based on the type of crop.